A leitura na formação de futuros professores: uma proposta integrada - Rodrigues, Cátia (2011)
This thesis is situated in the field of Reading Skils and has the importance of such skills in the teacher s initial formation as a theme. The following study starts from the assumption that reading proficiency is an essential skill for the future teacher s formation. Our aim here is to delineate the profile of the student that reaches College Education and follows an Teacher Education Program and to present a proposition for the future teacher s formation which can, being integrated to the undergraduation program, improve the student s reading skills. In order to fulfil the above proposed objetives we will search epistemological base for this study in the Textual Linguistic, especially in the work of Koch (2004, 2006, 2007), Marcuschi (2008), Adam (2008 e 2010), Beaugrande (1997) and Van Dijk (1996 e 2004). What makes our work important and justifies it from an academic point of view is the fact that the improvement of the educational process as a hole has increasingly become dependent on the quality of the teacher s initial formation. The set of questions used in this work to establish the profile of the future teacher and the undergraduation courses offered will help to increase the reading skills of the undergraduates from the Teacher Education Programs